Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
Step-by-step explanation:
x+i*y≠0 ==> x≠0 and y≠0
x-i*y≠0 ==> x≠0 and y≠0
We must exclude (0,0) as solution.
[tex]\dfrac{1}{x+i*y} +\dfrac{2}{x-i*y} =1+i\\\\\dfrac{1*(x-i*y)}{(x+i*y)(x-i*y)} +\dfrac{2*(x+i*y)}{(x-i*y)(x+i*y)} =1+i\\\\\\\dfrac{x-i*y+2x+2i*y}{x^2+y^2} =1+i\\\\3x+i*y=(1+i)(x^2+y^2)\\\\3x+i*y=(x^2+y^2)+i(x^2+y^2+i*(x^2+y^2)\\\\\left\{\begin{array}{ccc}3x&=&x^2+y^2\\y&=&x^2+y^2\\\end {array}\right.\\\\\\\left\{\begin{array}{ccc}y&=&3x\\3x&=&x^2+9x^2\\\end {array}\right.\\\\\\\left\{\begin{array}{ccc}y&=&3x\\x(10x-3)&=&0\\\end {array}\right.\\\\[/tex]
[tex]\left\{\begin{array}{ccc}x&=&0\\y&=&0\\\end {array}\right.\ (to\ exclude) \ or \ \left\{\begin{array}{ccc}x&=&\dfrac{3}{10}\\\\y&=&\dfrac{9}{10}\\\end {array}\right.\\\\Sol=\{(\dfrac{3}{10},\dfrac{9}{10})\}\\[/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.